Climate Change, Conflicts, and Forced Migration in the Middle East (2006-2022) - Zaouaq, Karim (WIMAYA, 2024)
In the Middle East region, the repercussions of climate change on migration and conflicts are increasingly perceived as a security issue as long as it’s so far among the world’s most impacted regions by water scarcity, rising temperatures, desertification, aridity, and food insecurity. This research is based on a literature review of articles published from 2006 to 2022, to understand the relationship between climate change, conflicts and forced migration in the Middle East. It examines the climate factors and their impacts on conflicts eruption or resurgence, and people’s livelihood in the Middle East region. The findings show that climate change increases people’s vulnerability in the Middle East and drive them to migration which represents then an adaptation strategy. This review finds also that the literature has not established a strong connection between climate change and conflicts, neither between these two drivers and forced migration. However, there’s a consensus among literature that the links between climate change, conflicts and forced migration in the Middle East region should not be omitted or neglected.